High-temperature-resistant iron-chromium black pigment as well as preparation method and application thereof

By sedimentary iron chromium black chromium black chromium black chromium black chromium black chromium in the surface of the porous SiO2/Al2O3 nano -ball, and combined with polynabine modifiers, the existing iron chromium black pigments were insufficient at high temperature resistance and flame retardant performance at high temperature. The problem realizes higher -performance iron chromium black pigments.

CN119371839AActive Publication Date: 2025-01-28HUNAN HUIBANG ENVIRONMENTAL PROTECTION TECH CO LTD

Patent Information

Application Number
CN202411945046.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-01-28
Estimated Expiration
2044-12-27

AI Technical Summary

Technical Problem

The existing iron-chromium black pigments have insufficient heat resistance and flame retardant properties at high temperatures, and have high production costs.

Method used

By preparing a porous SiO2/Al2O3 nanomal ball, and sedimentation of iron chromium black chromium at the surface of its surface, the sedimentation and high temperature burn are then performed. Finally, the time to improve the time and light resistance of the pigment through polybabine.

Benefits of technology

It significantly improves the high temperature resistance, heat resistance, flame retardant performance of iron chromium black pigments, and uniform particle size, uniform color, good dispersability, and suitable for high -performance coatings and plastic fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention provides a high-temperature-resistant iron-chromium black pigment as well as a preparation method and application thereof, and belongs to the technical field of pigments. The preparation method comprises the following steps: preparing porous SiO2 / Al2O3 nanospheres, modifying the surfaces of the porous SiO2 / Al2O3 nanospheres by using tannic acid, depositing iron-containing and chromium-containing precipitates in situ, impregnating zirconium, calcining to obtain a precursor, and modifying the surfaces of the porous SiO2 / Al2O3 nanospheres by using polydopamine to obtain the high-temperature-resistant iron-chromium black pigment. The high-temperature-resistant iron-chromium black pigment prepared by the preparation method disclosed by the invention contains an aluminum element, so that the high-temperature-resistant, heat-resistant and flame-retardant properties of a prepared precursor are greatly improved, and the high-temperature-resistant iron-chromium black pigment contains silicon oxide, so that the temperature resistance and the wear resistance are obviously improved, and the high-temperature-resistant iron-chromium black pigment is relatively uniform in black, uniform in particle size, good in weather resistance and light resistance, good in dispersity and wide in application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of pigments, and in particular to a high temperature resistant iron chrome black pigment and a preparation method and application thereof. Background Art

[0002] Iron chrome black has a unique brownish black color with a bright tone. It is a high-performance environmentally friendly metal oxide mixed phase pigment, which is suitable for the high-performance requirements of modern coatings and plastics. It is suitable for almost all plastics, paints and coatings, and is an internationally recognized non-toxic and environmentally friendly pigment. It has excellent weather resistance, light resistance, sun resistance, high temperature resistance, acid and alkali resistance, corrosion resistance, heat stability, and chemical resistance; strong covering power, environmentally friendly and non-toxic, no migration, no color bleeding, easy to disperse, high temperature oxidation resistance, insoluble in water and organic solvents, etc., and does not fade in outdoor use for 20 years; among the known inorganic pigments, organic pigments and dyes, the resistance of metal oxide mixed phase pigments is the highest, and it is these characteristics that determine its value in application products such as super-durable coatings and plastic products. In addition, metal oxide mixed phase pigments have special far-infrared protection functions, so they are particularly suitable for fields such as architectural coatings, and have excellent heat insulation, cooling, environmental protection and energy saving effects.

[0003] Iron chrome black is a mixed oxide formed by solid solution of Fe2O3 and Cr2O3 in a certain proportion, still maintaining the hematite structure, and its color is black with a reddish phase. Its composition can be expressed as Cr x Fe 2-x O3. Iron chrome black is the type of black pigment with the highest total solar reflectance (TSR value is close to 30%, while carbon black and copper chrome black TSR is about 5%). It has excellent weather resistance and light resistance, high temperature resistance, acid and alkali resistance, environmental protection and non-toxicity, no migration, no color bleeding, insoluble in water and organic solvents. Its color spectrum ranges from reddish brown to brownish black. It can be used for heat insulation and cooling coatings, coil coatings, powder coatings, transportation vehicle coatings, outdoor building coatings, camouflage coatings, painting coatings, road sign coatings, engineering plastics, general plastics, toy plastics, food packaging plastics, printing inks, masterbatches, high-performance industrial coatings, used in cement, concrete, roofing materials and other building materials, as well as ceramics.

[0004] At present, the main processes for producing iron chrome black include solid phase synthesis, coprecipitation and sol-gel. Among them, the solid phase synthesis method is widely adopted by major inorganic pigment manufacturers at home and abroad because it is easy to industrialize and has low cost. In the process of producing iron chrome black pigment by solid phase method, iron oxide, chromium oxide and a small amount of additives are first mixed evenly, and then the finished product is obtained by high temperature calcination-crushing-rinsing-drying-ultrafine grinding. Restricted by the crushing capacity of ultrafine grinding equipment, the average particle size of iron chrome black produced by domestic manufacturers is mostly above 1.0μm. Even the star companies in the inorganic pigment industry such as Shepherd Color in the United States can only reach an average particle size of 0.7μm for similar products. Sol-gel method is a common process for synthesizing nanopowders. The particle size of iron chrome black pigment synthesized by this method is mostly less than 200nm.

[0005] Chinese invention patent CN107628646B discloses an iron chrome black pigment and its preparation method, which uses Cr(NO3)3·9H2O and Fe(NO3)3·9H2O to mix and concentrate, and then self-propagating reaction and high-temperature calcination to obtain iron chrome black pigment. The iron chrome black pigment prepared by this invention application has high infrared reflectivity, complete grains and concentrated distribution in the submicron range, and is suitable for coatings, plastics, inks and other industries. However, this invention requires the use of Cr(NO3)3·9H2O and Fe(NO3)3·9H2O to prepare a Cr / Fe aqueous solution, and the raw materials need to be specially prepared, resulting in a high production cost.

[0006] Chinese invention patent application CN102351247A discloses a method for producing chromium oxide black using sodium bisulfate, a byproduct of chromic anhydride. The method uses sodium bisulfate, a byproduct of chromic anhydride, and scrap iron as raw materials, uses the scrap iron to reduce the hexavalent chromium in the sodium bisulfate, and then uses alkali to form a coprecipitate, and calcines at high temperature to obtain iron chrome black. The method uses sodium bisulfate, a byproduct of chromic anhydride, and scrap iron as raw materials to prepare iron chrome black, and makes good use of the chromic anhydride byproduct. However, the coprecipitation process of the invention consumes a large amount of alkali and generates saline wastewater. The obtained coprecipitate increases energy consumption during drying or calcining, resulting in increased costs. Summary of the invention

[0007] The purpose of the present invention is to provide a high-temperature resistant iron chrome black pigment and a preparation method and application thereof, which improves the high-temperature resistance, heat resistance and flame retardancy of the prepared precursor, significantly improves the wear resistance, and has a more uniform black color, uniform particle size, good weather resistance and light resistance, good dispersibility, and broad application prospects.

[0008] The technical solution of the present invention is achieved in this way: The invention provides a method for preparing a high temperature resistant iron chrome black pigment. The method comprises the following steps: preparing porous SiO2 / Al2O3 nanospheres, modifying the surface of the nanospheres with tannic acid, depositing iron and chromium precipitates in situ, impregnating zirconium, calcining, obtaining a precursor, and modifying the surface of the nanospheres with polydopamine to obtain the high temperature resistant iron chrome black pigment. The method comprises the following steps: S1. Preparation of porous SiO2 / Al2O3 nanospheres: adding alkyl orthosilicate and aluminum isopropoxide to ethanol, adding ammonia water, a porogen and water, heating and stirring to react, centrifuging, washing, drying and calcining to obtain porous SiO2 / Al2O3 nanospheres; S2. Tannic acid modification: adding porous SiO2 / Al2O3 nanospheres to water, adding tannic acid and a catalyst, heating and stirring to react, centrifuging, washing, and drying to obtain tannic acid-modified porous SiO2 / Al2O3 nanospheres; S3. In-situ generation of iron chrome black: dissolving iron salt and chromium salt in water, adding tannic acid-modified porous SiO2 / Al2O3 nanospheres, stirring and mixing, adjusting the pH value of the solution, standing and settling, centrifuging, washing, and drying to obtain a precursor; S4. Zirconium deposition: dissolving zirconium chloride in water, adding a precursor, impregnating, centrifuging, washing, and drying to obtain a zirconium deposition precursor; S5. Calcination: The zirconium deposition precursor is heated and calcined to obtain an iron chrome black pigment; S6. Polydopamine modification: Add iron chrome black pigment into water, add dopamine hydrochloride and catalyst, heat and stir to react, centrifuge, wash and dry to obtain high temperature resistant iron chrome black pigment.

[0009] As a further improvement of the present invention, the alkyl orthosilicate in step S1 is methyl orthosilicate or ethyl orthosilicate, the mass ratio of the alkyl orthosilicate, aluminum isopropoxide, ethanol, ammonia water, porogen and water is 5-7:3-5:70-100:8-12:1-2:5-7, the porogen is hexadecyltrimethylammonium chloride or hexadecyltrimethylammonium bromide, the temperature of the heating and stirring reaction is 50-60°C, the time is 7-10h, the calcination temperature is 600-800°C, and the time is 2-4h.

[0010] As a further improvement of the present invention, the mass ratio of the porous SiO2 / Al2O3 nanospheres, tannic acid and catalyst in step S2 is 12-15:4-6:1-2, the catalyst is a Tris-HCl solution with a pH of 8.5-9.5, the temperature of the heating and stirring reaction is 40-50°C, and the time is 3-5h.

[0011] As a further improvement of the present invention, the iron salt in step S3 is ferric nitrate, ferric chloride or ferric sulfate, the chromium salt is chromium nitrate, the mass ratio of the iron salt, chromium salt and tannic acid modified porous SiO2 / Al2O3 nanospheres is 2.2-2.7:4.5-5:5, and the pH value of the adjusted solution is 9-10.

[0012] As a further improvement of the present invention, in step S4, the mass ratio of zirconium chloride to precursor is 1-2:10, and the immersion time is 1-2 hours.

[0013] As a further improvement of the present invention, the heating and calcining in step S5 is carried out at a temperature of 850-950° C. and for a time of 1-3 h.

[0014] As a further improvement of the present invention, the mass ratio of the iron chrome black pigment, dopamine hydrochloride and the catalyst in step S6 is 10:2-3:0.2-0.5, the catalyst is a Tris-HCl solution with a pH of 8.5-9.5, the temperature of the heating and stirring reaction is 45-55° C., and the time is 2-4 hours.

[0015] The present invention further protects a high temperature resistant iron chrome black pigment prepared by the above preparation method.

[0016] The present invention further protects the use of the above-mentioned high temperature resistant iron chrome black pigment in the preparation of infrared reflecting paint.

[0017] The present invention has the following beneficial effects: The present invention prepares porous SiO2 / Al2O3 nanospheres through sol-gel reaction under the action of a porogen. The surface of the nanospheres is provided with abundant pores, which increases the specific surface area of ​​the nanospheres and is conducive to the uniform deposition of metal ions. The prepared nanospheres have uniform particle sizes. After surface modification by tannic acid, the surface of the nanospheres has abundant carboxyl groups, which can form complex bonds with metal ions to adsorb iron and chromium ions on the surface of the nanospheres. After the solution environment is adjusted to be alkaline, the iron and chromium ions can be precipitated in situ on the surface of the nanospheres, so that the particle size of the prepared precursor is uniform and spherical, and has good visible-infrared light reflection performance.

[0018] After impregnating and depositing zirconium on the surface of the prepared precursor, the weather resistance, light resistance and wear resistance of the prepared pigment can be greatly improved. After high-temperature calcination, zirconium-doped iron chrome black pigment is obtained. At this time, tannic acid is carbonized into black carbon attached to the nanospheres, further improving the wear resistance of the pigment and the visible-infrared light reflection performance of the pigment.

[0019] After the surface of the prepared iron chrome black pigment is modified by polydopamine, the weather resistance and light resistance of the pigment are significantly improved through the coating effect, which prevents direct ultraviolet radiation, isolates the pigment particles from the organic matter of the paint base, reduces the destructive power of photochemical action, and thus improves the weather resistance and light resistance of the pigment. In addition, the modification of polydopamine can also significantly improve the dispersion uniformity of the pigment in the paint base organic matter, effectively avoid the aggregation of the pigment, and improve the applicability.

[0020] The high temperature resistant iron chrome black pigment prepared by the invention contains aluminum element, thereby greatly improving the high temperature resistance, heat resistance and flame retardancy of the prepared precursor, and contains silicon oxide, so that the temperature resistance and wear resistance are significantly improved, and the black color is more uniform, the particle size is uniform, the weather resistance and light resistance are good, and the dispersibility is good, and the pigment has broad application prospects. DETAILED DESCRIPTION

[0021] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0022] Example 1 The present embodiment provides a method for preparing a high temperature resistant iron chrome black pigment, comprising the following steps: S1. Preparation of porous SiO2 / Al2O3 nanospheres: 5 g of methyl orthosilicate and 3 g of aluminum isopropoxide were added to 70 g of ethanol, 8 g of ammonia water, 1 g of hexadecyltrimethylammonium chloride and 5 g of water, heated to 50°C, stirred for 7 h, centrifuged, washed, dried, and calcined at 600°C for 2 h to obtain porous SiO2 / Al2O3 nanospheres; S2. Tannic acid modification: 12 g of porous SiO2 / Al2O3 nanospheres were added to 200 mL of water, 4 g of tannic acid and 1 g of catalyst were added, heated to 40°C, stirred for 3 h, centrifuged, washed, and dried to obtain tannic acid-modified porous SiO2 / Al2O3 nanospheres; The catalyst is a Tris-HCl solution with a pH of 8.5; S3. In-situ generation of iron chrome black: 2.2 g of iron nitrate and 4.5 g of chromium nitrate were dissolved in 200 mL of water, 5 g of tannic acid-modified porous SiO2 / Al2O3 nanospheres were added, and the mixture was stirred for 15 min, the pH value of the solution was adjusted to 9, and the mixture was allowed to stand for 2 h, centrifuged, washed, and dried to obtain a precursor; S4 zirconium deposition: 1g zirconium chloride was dissolved in 100mL water, 10g of the precursor was added, immersed for 1h, centrifuged, washed, and dried to obtain a zirconium deposition precursor; S5. Calcination: The zirconium deposition precursor is heated to 850° C. and calcined for 1 h to obtain an iron chrome black pigment; S6. Polydopamine modification: 10 g of iron chrome black pigment was added to 200 mL of water, 2 g of dopamine hydrochloride and 0.2 g of catalyst were added, heated to 45°C, stirred for reaction for 2 h, centrifuged, washed, and dried to obtain a high temperature resistant iron chrome black pigment; The catalyst is a Tris-HCl solution with a pH of 8.5.

[0023] Example 2 The present embodiment provides a method for preparing a high temperature resistant iron chrome black pigment, comprising the following steps: S1. Preparation of porous SiO2 / Al2O3 nanospheres: 7 g of tetraethyl orthosilicate and 5 g of aluminum isopropoxide were added to 100 g of ethanol, 12 g of ammonia water, 2 g of hexadecyltrimethylammonium bromide and 7 g of water were added, heated to 60°C, stirred for 10 h, centrifuged, washed, dried, and calcined at 800°C for 4 h to obtain porous SiO2 / Al2O3 nanospheres; S2. Tannic acid modification: 15 g of porous SiO2 / Al2O3 nanospheres were added to 200 mL of water, 6 g of tannic acid and 2 g of catalyst were added, heated to 50°C, stirred for 5 h, centrifuged, washed, and dried to obtain tannic acid-modified porous SiO2 / Al2O3 nanospheres; The catalyst is a Tris-HCl solution with a pH of 9.5; S3. In-situ generation of iron chrome black: 2.7 g of iron nitrate and 5 g of chromium nitrate were dissolved in 200 mL of water, 5 g of tannic acid-modified porous SiO2 / Al2O3 nanospheres were added, and the mixture was stirred for 15 min, the pH value of the solution was adjusted to 10, and the mixture was allowed to stand for 2 h, centrifuged, washed, and dried to obtain a precursor; S4 zirconium deposition: 2g zirconium chloride was dissolved in 100mL water, 10g of the precursor was added, immersed for 2h, centrifuged, washed, and dried to obtain a zirconium deposition precursor; S5. Calcination: The zirconium deposition precursor was heated to 950°C and calcined for 3h to obtain an iron chrome black pigment; S6. Polydopamine modification: 10 g of iron chrome black pigment was added to 200 mL of water, 3 g of dopamine hydrochloride and 0.5 g of catalyst were added, heated to 55°C, stirred for 4 h, centrifuged, washed, and dried to obtain a high temperature resistant iron chrome black pigment; The catalyst is a Tris-HCl solution with a pH of 9.5.

[0024] Example 3 The present embodiment provides a method for preparing a high temperature resistant iron chrome black pigment, comprising the following steps: S1. Preparation of porous SiO2 / Al2O3 nanospheres: 6 g of tetraethyl orthosilicate and 4 g of aluminum isopropoxide were added to 85 g of ethanol, 10 g of ammonia water, 1.5 g of hexadecyltrimethylammonium bromide and 6 g of water were added, heated to 55°C, stirred for 8 h, centrifuged, washed, dried, and calcined at 700°C for 3 h to obtain porous SiO2 / Al2O3 nanospheres; S2. Tannic acid modification: 13 g of porous SiO2 / Al2O3 nanospheres were added to 200 mL of water, 5 g of tannic acid and 1.5 g of catalyst were added, heated to 45°C, stirred for 4 h, centrifuged, washed, and dried to obtain tannic acid-modified porous SiO2 / Al2O3 nanospheres; The catalyst is a Tris-HCl solution with a pH of 9; S3. In-situ generation of iron chrome black: 2.5 g of iron nitrate and 4.7 g of chromium nitrate were dissolved in 200 mL of water, 5 g of tannic acid-modified porous SiO2 / Al2O3 nanospheres were added, and the mixture was stirred for 15 min, the pH value of the solution was adjusted to 9.5, and the mixture was allowed to settle for 2 h, centrifuged, washed, and dried to obtain a precursor; S4 zirconium deposition: 1.5 g zirconium chloride was dissolved in 100 mL water, 10 g of the precursor was added, immersed for 1.5 h, centrifuged, washed, and dried to obtain a zirconium deposition precursor; S5. Calcination: The zirconium deposition precursor is heated to 900° C. and calcined for 2 h to obtain an iron chrome black pigment; S6. Polydopamine modification: 10 g of iron chrome black pigment was added to 200 mL of water, 2.5 g of dopamine hydrochloride and 0.35 g of catalyst were added, heated to 50°C, stirred for 3 h, centrifuged, washed, and dried to obtain a high temperature resistant iron chrome black pigment; The catalyst is a Tris-HCl solution with a pH of 9.

[0025] Comparative Example 1 Compared with Example 3, the difference is that aluminum isopropoxide is not added in step S1.

[0026] The details are as follows: S1. Preparation of porous SiO2 nanospheres: 10 g of tetraethyl orthosilicate was added to 85 g of ethanol, 10 g of ammonia water, 1.5 g of hexadecyltrimethylammonium bromide and 6 g of water, heated to 55°C, stirred for reaction for 8 h, centrifuged, washed, dried, and calcined at 700°C for 3 h to obtain porous SiO2 nanospheres.

[0027] Comparative Example 2 Compared with Example 3, the difference is that no porogen is added in step S1.

[0028] The details are as follows: S1. Preparation of SiO2 / Al2O3 nanospheres: Add 6 g of tetraethyl orthosilicate and 4 g of aluminum isopropoxide to 85 g of ethanol, add 10 g of ammonia water and 6 g of water, heat to 55°C, stir and react for 8 h, centrifuge, wash, dry, and calcine at 700°C for 3 h to obtain SiO2 / Al2O3 nanospheres.

[0029] Comparative Example 3 Compared with Example 3, the difference is that step S2 is not performed.

[0030] The details are as follows: S1. Preparation of porous SiO2 / Al2O3 nanospheres: 6 g of tetraethyl orthosilicate and 4 g of aluminum isopropoxide were added to 85 g of ethanol, 10 g of ammonia water, 1.5 g of hexadecyltrimethylammonium bromide and 6 g of water were added, heated to 55°C, stirred for 8 h, centrifuged, washed, dried, and calcined at 700°C for 3 h to obtain porous SiO2 / Al2O3 nanospheres; S2. In-situ generation of iron chrome black: 2.5 g of iron nitrate and 4.7 g of chromium nitrate were dissolved in 200 mL of water, 5 g of porous SiO2 / Al2O3 nanospheres were added, and the mixture was stirred for 15 min. The pH value of the solution was adjusted to 9.5, and the mixture was allowed to stand for 2 h. The mixture was centrifuged, washed, and dried to obtain a precursor. S3 zirconium deposition: 1.5 g zirconium chloride was dissolved in 100 mL water, 10 g of the precursor was added, immersed for 1.5 h, centrifuged, washed, and dried to obtain a zirconium deposition precursor; S4. Calcination: The zirconium deposition precursor is heated to 900° C. and calcined for 2 h to obtain an iron chrome black pigment; S5. Polydopamine modification: 10 g of iron chrome black pigment was added to 200 mL of water, 2.5 g of dopamine hydrochloride and 0.35 g of catalyst were added, heated to 50°C, stirred for 3 h, centrifuged, washed, and dried to obtain a high temperature resistant iron chrome black pigment; The catalyst is a Tris-HCl solution with a pH of 9.

[0031] Comparative Example 4 Compared with Example 3, the difference is that step S4 is not performed.

[0032] The details are as follows: S1. Preparation of porous SiO2 / Al2O3 nanospheres: 6 g of tetraethyl orthosilicate and 4 g of aluminum isopropoxide were added to 85 g of ethanol, 10 g of ammonia water, 1.5 g of hexadecyltrimethylammonium bromide and 6 g of water were added, heated to 55°C, stirred for 8 h, centrifuged, washed, dried, and calcined at 700°C for 3 h to obtain porous SiO2 / Al2O3 nanospheres; S2. Tannic acid modification: 13 g of porous SiO2 / Al2O3 nanospheres were added to 200 mL of water, 5 g of tannic acid and 1.5 g of catalyst were added, heated to 45°C, stirred for 4 h, centrifuged, washed, and dried to obtain tannic acid-modified porous SiO2 / Al2O3 nanospheres; The catalyst is a Tris-HCl solution with a pH of 9; S3. In-situ generation of iron chrome black: 2.5 g of iron nitrate and 4.7 g of chromium nitrate were dissolved in 200 mL of water, 5 g of tannic acid-modified porous SiO2 / Al2O3 nanospheres were added, and the mixture was stirred for 15 min, the pH value of the solution was adjusted to 9.5, and the mixture was allowed to settle for 2 h, centrifuged, washed, and dried to obtain a precursor; S4. Calcination: The precursor is heated to 900°C and calcined for 2h to obtain an iron chrome black pigment; S5. Polydopamine modification: 10 g of iron chrome black pigment was added to 200 mL of water, 2.5 g of dopamine hydrochloride and 0.35 g of catalyst were added, heated to 50°C, stirred for 3 h, centrifuged, washed, and dried to obtain a high temperature resistant iron chrome black pigment; The catalyst is a Tris-HCl solution with a pH of 9.

[0033] Comparative Example 5 Compared with the embodiment 3, the difference is that step S6 is not performed.

[0034] The details are as follows: S1. Preparation of porous SiO2 / Al2O3 nanospheres: 6 g of tetraethyl orthosilicate and 4 g of aluminum isopropoxide were added to 85 g of ethanol, 10 g of ammonia water, 1.5 g of hexadecyltrimethylammonium bromide and 6 g of water were added, heated to 55°C, stirred for 8 h, centrifuged, washed, dried, and calcined at 700°C for 3 h to obtain porous SiO2 / Al2O3 nanospheres; S2. Tannic acid modification: 13 g of porous SiO2 / Al2O3 nanospheres were added to 200 mL of water, 5 g of tannic acid and 1.5 g of catalyst were added, heated to 45°C, stirred for 4 h, centrifuged, washed, and dried to obtain tannic acid-modified porous SiO2 / Al2O3 nanospheres; The catalyst is a Tris-HCl solution with a pH of 9; S3. In-situ generation of iron chrome black: 2.5 g of iron nitrate and 4.7 g of chromium nitrate were dissolved in 200 mL of water, 5 g of tannic acid-modified porous SiO2 / Al2O3 nanospheres were added, and the mixture was stirred for 15 min, the pH value of the solution was adjusted to 9.5, and the mixture was allowed to settle for 2 h, centrifuged, washed, and dried to obtain a precursor; S4 zirconium deposition: 1.5 g zirconium chloride was dissolved in 100 mL water, 10 g of the precursor was added, immersed for 1.5 h, centrifuged, washed, and dried to obtain a zirconium deposition precursor; S5. Calcination: The zirconium deposition precursor is heated to 900° C. and calcined for 2 hours to obtain an iron chrome black pigment, namely, a high temperature resistant iron chrome black pigment.

[0035] Test Example 1 The infrared reflection performance of the high temperature resistant iron chrome black pigments prepared in Examples 1-3 or Comparative Examples 1-5 was tested using a Lambda 950 visible-near infrared spectrometer from PerkinElmer, USA. The reflectivity of light with wavelengths of 700 nm and 1500 nm was tested. The results are shown in Table 1.

[0036] Table 1

[0037] It can be seen from the above table that the high temperature resistant iron chrome black pigments prepared in Examples 1-3 of the present invention have good visible-infrared light reflection performance.

[0038] Test Example 2 The HP-200 precision colorimeter of Shanghai Hanpu Optoelectronics Technology Co., Ltd. was used to measure the lightness L*, red-green property a* and yellow-blue property b* of the high-temperature resistant iron chrome black pigments prepared in Examples 1-3 or Comparative Examples 1-5. The results are shown in Table 2.

[0039] Table 2

[0040] It can be seen from the above table that the color of the high temperature resistant iron chrome black pigment prepared in Examples 1-3 of the present invention is close to pure black.

[0041] Test Example 3 The comprehensive properties of the high temperature resistant iron chrome black pigments prepared in Examples 1-3 or Comparative Examples 1-5 were tested, and the results are shown in Table 3.

[0042] Table 3

[0043] It can be seen from the above table that the high temperature resistant iron chrome black pigments prepared in Examples 1-3 of the present invention have good heat resistance, light resistance and weather resistance.

[0044] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a high temperature resistant iron chrome black pigment, characterized in that: The porous SiO2 / Al2O3 nanospheres are prepared, the surface is modified by tannic acid, iron and chromium precipitates are deposited in situ, zirconium is impregnated, and calcined to obtain a precursor, and the surface is modified by polydopamine to obtain a high temperature resistant iron chrome black pigment, which specifically includes the following steps: S1. Preparation of porous SiO2 / Al2O3 nanospheres: adding alkyl orthosilicate and aluminum isopropoxide to ethanol, adding ammonia water, a porogen and water, heating and stirring to react, centrifuging, washing, drying and calcining to obtain porous SiO2 / Al2O3 nanospheres; S2. Tannic acid modification: adding porous SiO2 / Al2O3 nanospheres to water, adding tannic acid and a catalyst, heating and stirring to react, centrifuging, washing, and drying to obtain tannic acid-modified porous SiO2 / Al2O3 nanospheres; S3. In-situ generation of iron chrome black: dissolving iron salt and chromium salt in water, adding tannic acid-modified porous SiO2 / Al2O3 nanospheres, stirring and mixing, adjusting the pH value of the solution, standing and settling, centrifuging, washing, and drying to obtain a precursor; S4. Zirconium deposition: dissolving zirconium chloride in water, adding a precursor, impregnating, centrifuging, washing, and drying to obtain a zirconium deposition precursor; S5. Calcination: The zirconium deposition precursor is heated and calcined to obtain an iron chrome black pigment; S6. Polydopamine modification: Add iron chrome black pigment into water, add dopamine hydrochloride and catalyst, heat and stir to react, centrifuge, wash and dry to obtain high temperature resistant iron chrome black pigment.

2. The preparation method according to claim 1, characterized in that: In step S1, the alkyl orthosilicate is methyl orthosilicate or ethyl orthosilicate, the mass ratio of the alkyl orthosilicate, aluminum isopropoxide, ethanol, ammonia water, porogen and water is (5-7): (3-5): (70-100): (8-12): (1-2): (5-7), the porogen is hexadecyltrimethylammonium chloride or hexadecyltrimethylammonium bromide, the temperature of the heating and stirring reaction is 50-60°C, the time is 7-10h, and the temperature of the calcination is 600-800°C, and the time is 2-4h.

3. The preparation method according to claim 1, characterized in that: The mass ratio of the porous SiO2 / Al2O3 nanospheres, tannic acid and catalyst in step S2 is (12-15): (4-6): (1-2), the catalyst is a Tris-HCl solution with a pH of 8.5-9.5, the temperature of the heating and stirring reaction is 40-50°C, and the time is 3-5h.

4. The preparation method according to claim 1, characterized in that: In step S3, the iron salt is iron nitrate, iron chloride or iron sulfate, the chromium salt is chromium nitrate, the mass ratio of the iron salt, the chromium salt and the tannic acid modified porous SiO2 / Al2O3 nanospheres is (2.2-2.7): (4.5-5): 5, and the pH value of the adjusted solution is 9-10.

5. The preparation method according to claim 1, characterized in that: In step S4, the mass ratio of zirconium chloride to the precursor is 1-2:10, and the immersion time is 1-2 hours.

6. The preparation method according to claim 1, characterized in that: The heating and calcining in step S5 is carried out at a temperature of 850-950° C. and for a time of 1-3 hours.

7. The preparation method according to claim 1, characterized in that: In step S6, the mass ratio of the iron chrome black pigment, dopamine hydrochloride and the catalyst is 10:(2-3):(0.2-0.5), the catalyst is a Tris-HCl solution with a pH of 8.5-9.5, the temperature of the heating and stirring reaction is 45-55° C., and the time is 2-4 hours.

8. A high temperature resistant iron chrome black pigment obtained by the preparation method according to any one of claims 1 to 7.

9. Use of the high temperature resistant iron chrome black pigment as claimed in claim 8 in the preparation of infrared reflecting paint.

Citation Information

Patent Citations

  • Method of producing eriochrome black with sodium bisulfate, byproduct of chromic trioxide

    CN102351247A

  • A chromium iron black pigment and its preparation method

    CN107628646B

  • High temperature resistant pearlescent pigment and preparation method thereof

    CN104327552A

  • Black Fe-Cr pigment and preparation method thereof

    CN107628646A

  • Infrared reflection pigment as well as preparation method and application thereof

    CN117304713A

Cited By

  • Modified nano rare earth oxide compound as well as preparation method and application thereof

    CN121045963A

  • Modified nanometer rare earth oxide composite, and preparation method and application thereof

    CN121045963B